(untitled) (Journal of Comparative & International Higher Education, 2023)
A lack of consciousness about how the academic world operates results in misunderstandings among international students. In the present research, which was carried out at a private university in Ontario, we looked at international students’ understanding of basic academic regulations as the central point. To study international students’ understanding of academic rules, the contents of 3,438 student emails sent between January 2018 and December 2019 were qualitatively analyzed. Based on the research data, two main cultural features defined students’ understanding of basic academic regulations: • Students used a constellation of arguments to make requests/complaints. The students seemed not to be aware that their requests/complaints should be guided by the university’s formal regulations. • The variety of arguments developed by international students shows that the new academic environment is perceived as being governed by a complex set of informal regulations instead of being limited by institutional rules and regulations.